PENGENDALIAN PENYAKIT JAMUR AKAR PUTIH (JAP) PADA TANAMAN KARET RAKYAT DENGAN FUNGISIDA HAYATI JAMUR ANTAGONIS Trichoderma spp. - Morina Adfa; Welly Darwis; Irfan Gustian; Hendri Bustamam (DHARMA RAFLESIA, 2018)
The main problem in the people’s rubber in the village of Genting Perangkap and Lubuk Balam, Air Besi, North Bengkulu is a fungal disease that attacks the roots of plants. White root fungus disease (JAP) cause of death in rubber, so that the disease attacks resulted in significant losses. Based on field survey team PPM to land smallholder rubber of Genting Perangkap and Lubuk Balam Village, many found the plants spaces are very close, the stump of a dead rubber tree attacked JAP left alone on the land, and the plants die immediately replaced with new seedlings without eradicate exhausted dead tree stump by JAP. As a result of this new plant will die after the age of 2 years or more, since contracted directly by the fungi Rigidoporus microporus that cause disease JAP from the ground and fungal spores contained in the rubber tree stumps that had not been cleaned. To help the problems of rubber farmers in the village of Genting Perangkap and Lubuk Balam, it is necessary to control training and extension activities of white root fungus disease (JAP) on smallholder rubber plant with a fungicide biological antagonist fungus Trichoderma spp. and the efforts of former rubber plantation land processing stricken JAP. The method used is counseling, training, and applications directly to the field. Having done this activity then: Service target communities have been able to recognize the early symptoms of fungal disease attacks the roots of white, rubber plant spacing was good, as well as the handling of the former rubber plantation land that was attacked by JAP. Target communities have learned how to control the disease by using the JAP antagonist fungus Trichoderma spp. Target communities already have the expertise and is able to reproduce itself Trichoderma spp. and how the application of the newly planted crops, and plants attacked JAP. The outcome of this IbM activity is the product of the fertilizer Trichoderma spp. Keywords: Farmers, JAP, Rigidoporus microporus, Trichoderma spp.